The Legacy Lead Deposition in Soils and Its Impact on Cognitive Function in Preschool-Aged Children in the United States - Karen Clay; Margarita Portnykh; Edson R. Severnini (Institute of Labor Economics (IZA), 2019)
Surface soil contamination has been long recognized as an important pathway of human lead exposure, and is now a worldwide health concern. This study estimates the causal effects of exposure to lead in topsoil on cognitive ability among 5-year-old children. We draw on individual level data from the 2000 U.S. Census, and USGS data on lead in topsoil covering a broad set of counties across the United States. Using an instrumental variable approach relying on the 1944 Interstate Highway System Plan, we find that higher lead in topsoil increases considerably the probability of 5-year-old boys experiencing cognitive difficulties such as learning, remembering, concentrating, or making decisions. Living in counties with topsoil lead concentration above the national median roughly doubles the probability of 5-year-old boys having cognitive difficulties. Nevertheless, it does not seem to affect 5-year-old girls, consistent with previous studies. Importantly, the adverse effects of lead exposure on boys are found even in counties with levels of topsoil lead concentration considered low by the guidelines from the U.S. EPA and state agencies. These findings are concerning because they suggest that legacy lead may continue to impair cognition today, both in the United States and in other countries that have considerable lead deposition in topsoil.
Keywords: N52; Q53; Q56; R11; I15; I18; I25; I28; 330; legacy lead in soil; cognition; pre-school children